Al-Mashaqqah Tajlib Al-Tays¬ir Makna Dan Implikasinya Dalam Pengembangan Ekonomi Islam - M. Dliyaul Muflihin (Universitas Islam Lamongan, 2018)
The problem of Islamic economics is also increasingly complex with the large number of banks. To meet the needs of transactions, banks have products that are offered to the public. In accordance with the function of the bank, namely collecting and distributing funds to the public. The purpose of channeling funds by Islamic banks is to support the implementation of development, improve justice, togetherness and equal distribution of people's welfare. This paper will answer what is the meaning of al-mashaqqah tajlib al-taysir and how do the Implications of al-mashaqqah tajlib al-taysir in the development of Islamic economy? The result of research shows that the meaning of the rule of al-mashaqqah tajlib al-taysir is the difficulty of bringing convenience. The point is that if implementing a provision of shara' mukallaf faces obstacles in the form of difficulties and limitations that exceed the limits of reasonable capabilities, then the difficulty automatically creates relief provisions. In other words, if we find difficulty in carrying out something that is to be sharia, then the difficulty becomes a justifiable cause to facilitate in carrying out something that is to be provision of sharia, so that we can continue to run the sharia of Allah easily. The implications raised by the rules of al-mashaqqah tajlib al-taysir are the determination of the law of Islamic financial institutions. This impact is seen when Islamic law allows transactions in Islamic banking financial institutions, so that the community will easily meet the needs by transacting with Islamic banking through contracts that have been agreed upon. Keywords: al-Mashaqqah Tajlib al-Taysir, Islamic Economic Development